Kazakhstan's revealed comparative advantage vis-à-vis the EU-27 - Arastou Khatibi (European Centre for International Political Economy (ECIPE), 2008)
Economic trade relations between Kazakhstan and the EU are becoming increasingly important, and much of this economic success is due to its rich energy resources and the government's efforts in restructuring its centrally planned economy towards a more free-market based economy. In spite of these achievements a number of challenges remain to be dealt with, and one of the most important is diversifying the economy. This paper aims to examine Kazakhstan's competitiveness vis-à-vis world exports to the EU-27 and intra-exports between the EU-27 member countries. The empirical analysis is based on Balassa's revealed comparative advantage (RCA) measure. The analysis reveals that although Kazakhstan shows a revealed comparative advantage in a number of sectors, its competitiveness has a falling trend in almost all sectors.
Keywords: C10; F12; F13; P20; 330; Kazakhstan-EU trade relation; Revealed comparative advantage; competitiveness